BRAF mutations in cutaneous melanoma: no correlation with histological prognostic factors or overall survival - Jung,Juliana Elizabeth (2010)
INTRODUCTION: Molecular biology techniques allow identification of molecular markers such as BRAF and c-Kit gene mutations in melanomas. Studies on genetic alterations in melanomas of South-American patients are sparse. OBJECTIVES: To identify the incidence of BRAF and c-Kit gene mutations in primary cutaneous melanomas in Brazilian patients and to evaluate pathogenetic and prognostic implications of these mutations correlating them with clinical and histopathological data. MATERIAL AND METHODS: Ninety-six surgical specimens of primary cutaneous melanoma and 15 corresponding metastasis were analyzed using TaqMan Real-Time polymerase chain reaction (PCR) assays. RESULTS: In comparison with the medical literature, a relatively low frequency of BRAF mutation in primary (39%) and metastatic (40%) melanomas and complete absence of c-Kit gene mutations were demonstrated. BRAF mutations arose at an early stage during melanoma progression and were not involved in the transition of thin (< 1 mm) to thick (> 1 mm) melanomas. BRAF mutations are related to patients' younger age and to the pattern of sun exposure, although there was no correlation with any histological prognostic factor or overall survival. CONCLUSION: The identification of both BRAF and c-Kit mutation is not a suitable prognostic indicator in the Brazilian population. Moreover, the relatively low frequency of BRAF mutations brings into question if it actually plays a key role in melanoma pathogenesis.